Histological and Histochemical Studies on the Mammary Gland of Malnad Gidda Cows of Karnataka - Naik, S Ganga; Prasad, R V; Jamuna, K V; Murthy, V Chandrashekar; Isloor, Shrikrishna; Ramesha, K P; Kotresh, A M; Ramkrishna, V (Indian Journal of Veterinary Anatomy, 2016)
The mammary gland of lactating Malnad Gidda cows was surrounded from outside to inside by the skin and the fibroelastic capsule. The epidermis of the skin was lined by stratified squamous keratinized epithelium. The dermis showed nerve fibres, sweat gland, sebaceous gland and hair follicles. The interstitial tissue of the mammary gland provided important structural support for the secretory units and contained blood vessels, lymph vessels and nerves. The interalveolar septum consisted of collagen, elastic and reticular fibres, fibroblasts and smooth muscle. The glandular epithelium was surrounded by reticular fibres with infiltration of lymphocytes, neutrophils, macrophages and plasma cells. The presence of higher number of immunogenic cells in the mammary gland might be responsible for extending higher resistance power to fight against mastitis and other diseases.The glandular alveoli were round to oval lined by simple cuboidal epithelium with supranuclear vacuolation, indicating supranuclear lipid accumulation. The gland was divided into lobes and lobules by the trabeculae extending from the capsule. The cells of the alveoli revealed presence of iron and calcium. The secretory materials showed presence of iron, mucopolysacharides, sulphated and acidic mucopolysacharides, fat and cholesterol. The corpora amylacea were dense bodies located in the alveoli, interalveolar, interlobular and interlobar connective tissue. The corpora amylacea were round, oval or irregular shaped concentrically laminated bodies with few droplets in the centre. The acidic and sulphated mucopolysacharides, proteins and mucin were seen in corpora amylacea.